Practical Cookery - Ceserani, Victor; Kinton, Ronald; Foskett, David, 1951- (London : Hodder & Stoughton, 2000)
The market-leading catering textbook for over 30 years, Practical Cookery has now been updated to include a full range of up-to-date recipes and methods, as well as to ensure a new look for the millennium.
Previous ed.: 1995.
Includes index.
Keywords: Cookery; Food and Drink